4: Birth Weight Below 500 Grams: Developmental Consequences. Issue 6 (1st June 2014) - Bashir, RA; Thomas, J Petrie; MacKay, M; Agnew, J; Hubber-Richard, P; Synnes, A
Abstract: BACKGROUND: Data on survival and morbidities of babies weighing <500 g at birth is needed for antenatal counseling and decision making regarding resuscitation. OBJECTIVES: To describe survival of babies <500 g birth weight (BW) born 1985–2012 and long term outcomes of babies born 1985–2008. DESIGN/METHODS: Institutional survival rates were calculated for all births and live births for epochs: 1985–87, 1988–92, 1993–97, 1998–2002, 2003–07 and 2008–12. Pregnancy terminations were excluded. All survivors with BW <500 g were invited to the Neonatal Follow-Up Program (NFUP). Birth characteristics and neurodevelopmental outcomes at 18 months (m) corrected age (CA) and at 4.5 years (yr) were evaluated and analyzed descriptively. Definitions: Cerebral palsy (CP) – abnormalities of tone and reflexes according to Bax; bilateral visual impairment; hearing impairment – hearing aid or cochlear implant prescribed. Motor impairment was defined at 18 m CA as <70 on the Bayley I, II or III; and at 4.5 yr as <70 on a motor quotient of the Peabody PDMS 1 or 2 and/or Developmental Coordination Disorder (DCD) as less than or equal to 5%le on Movement ABC I or II. Cognitive impairment was defined at 18 m CA as <70 on the BSID-I or II and adjusted Bayley-III score (Moore et al, 2012) and at 4.5 yr as <70 on Wechsler testing (WPPSI-R and WPPSI III). RESULTS: Survival rates were 2.7% for all births (according to epochs: 0.9%, 0%, 1.2%, 2.0%, 10.5% and 3.6%) and 6.6% for live births (according to epochs: 1.9%, 0%, 3.4%, 4.1%, 24% and 11.1%). Of 25 neonatal survivors, one died at 9 m CA (BW 492 g) and one refused follow-up. Data were extracted for 23 children. The earliest survivor was born in 1987 (male, BW 480 g). Babies had a median BW 465 g (range 380 g to 495 g), and gestation 26 1/7 weeks (range 22 4/7 to 30 2/7 weeks); 21 (84%) were inborn and 12 (48%) were male; 20% were of multiple pregnancy; 19 babies (76%) were small for gestational age (BW <3rd percentile). Median Apgar at 5 min was 7 (range 1 to 10).